Risk-benefit of Antithrombotic Treatment in Patients with Hemorrhage-prone Cerebral Small Vessel Disease - Balali, Pargol (My University, 2023)
Background: Cerebral microbleeds are asymptomatic neuroimaging markers of small vessel disease (SVD), visualized as small hypointensities on blood-sensitive magnetic resonance imaging (MRI) sequences. Patients with ischemic stroke and microbleeds are at a higher risk of future ischemic stroke and intracranial hemorrhage. Antithrombotic therapies, the mainstay treatment of secondary stroke prevention, are associated with an increased risk of bleeding. This raises concerns surrounding the net benefit of antithrombotic therapies in these hemorrhage-prone patients. The overarching aim of this thesis is to determine the safety of antithrombotic treatments in patients with hemorrhage-prone SVD marked by microbleeds on MRI or prior intracerebral hemorrhage (ICH). I aimed to characterize the association between baseline microbleeds and the risk of future clinical outcomes in patients with ischemic stroke and whether there exists treatment effect modification of different anticoagulants on clinical outcomes according to microbleeds presence, location, and number. Methods: We performed post hoc analyses on two multicenter previously conducted randomized trials in patients with non-cardioembolic ischemic stroke. For the PACIFIC-STROKE trial, we used multivariable regression models to determine the contribution of microbleeds to the risk of new microbleeds, hemorrhagic transformation (HT), ischemic stroke, intracranial hemorrhage, and death. We assessed the treatment effect of asundexian, a factor XIa inhibitor, vs. placebo on these clinical outcomes, stratified by microbleeds presence, location, and number. I was trained on standardized rating of microbleeds on MRI, achieved excellent interrater reliability, and rated all DATAS-II participant MRIs. I used multivariable logistic regression models to identify the association between microbleeds and HT and 90-day excellent functional outcome. I assessed the interaction between treatment with dabigatran, a direct thrombin inhibitor, vs. aspirin and microbleeds for these outcomes. Separately, I performed a review of the literature and wrote an editorial discussing the optimum timing of antiplatelet re-initiation after ICH. Results: The PACIFIC-STROKE post hoc analyses showed that microbleeds are associated with a 1.6-fold and 4.4-fold higher risk of HT and new microbleeds, respectively. The DATAS-II exploratory analyses demonstrated no association between the risk of outcomes and microbleeds presence. We found no interaction between treatment assignment and microbleed presence for any of the clinical outcomes investigated in either of these studies. Based on the totality of evidence, we concluded that early resumption of antiplatelets in ICH survivors is likely to be safe. Conclusion: Our findings do not support existing concerns surrounding the use of anticoagulants in patients with acute ischemic stroke and microbleeds on MRI, nor for the early resumption of antiplatelets in ICH survivors.
Balali_Pargol_MSc thesis_Neuroscience department_2023Sep
Keywords: Microbleeds; Ischemic stroke; Stroke prevention; Anticoagulation; Cerebral small vessel disease; Intracerebral hemorrhage